The Echoes of the Armenian Tragedy in Russian Poetry in the Second Half of the 20th Century - JANPOLADYAN, MAGDA (Bulletin of Yerevan University H: Russian Philology, 2021)
The subject of the article is the topic of the Armenian Genocide in the works of Russian poets, such as V. Zvyagintseva, A.Gitovich, A.Tarkovsky, M. Matusovsky, B. Chichibabin, M. Dudin and others. The author of the article shows that even decades after the Armenian Genocide it remained a matter of concern for Russian poets, becoming an integral part of their perception of Armenia’s and its people’s fate. The main motives of poems are distinguished, such as deep compassion for the Armenian tragedy, the impunity of Turkey as genocide com-mitter, hope for the restoration of historical justice, the vitality of the Armenian people and their love for life.
Keywords: Genocide, memory, monstrous crime, compassion, falsification of history, vi-tality of people